2015
DOI: 10.1016/j.addbeh.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Everyday discrimination and mood and substance use disorders: A latent profile analysis with African Americans and Caribbean Blacks

Abstract: Perceived discrimination is a major source of health-related stress. The purpose of this study was to model the heterogeneity of everyday-discrimination experiences among African American and Caribbean Blacks and to identify differences in the prevalence of mood and substance use outcomes, including generalized anxiety disorder, major depressive disorder, alcohol-use disorder, and illicit drug-use disorder among the identified subgroups. The study uses data from the National Survey of American Life obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 24 publications
6
61
0
1
Order By: Relevance
“…Notably, immigrant youth were more likely to experience bullying related to religious or racial factors. Bullying based on racial/ethnic differences is particularly noteworthy given recent research on the links between discrimination and acculturation with mental health and maladjustment among minority populations [7, 36-37]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, immigrant youth were more likely to experience bullying related to religious or racial factors. Bullying based on racial/ethnic differences is particularly noteworthy given recent research on the links between discrimination and acculturation with mental health and maladjustment among minority populations [7, 36-37]. …”
Section: Discussionmentioning
confidence: 99%
“…The prior decade has ushered in social change linked to race in the United States, coupled with a widespread recession that was worse economically for African American families (Kochhar and Fry, 2014), and ongoing political unrest due to high profile aggressive policing tactics (Jee-Lyn Garcia and Sharif, 2015). We can only speculate about whether and how these broader changes may affect minority students differently than White students, though we might expect recession and political unrest to increase perceived stress, discrimination, and vulnerability among disadvantaged minority students in particular, three risk factors for initiation and continued use of illicit substances (Clark, 2014; Clark et al, 2015; Sinha, 2008). Such stressors may not extend to adolescents attending school; continued research into motivations for use of marijuana and other substances, and how they might differ over time across race and ethnic groups with differential exposures to stress, is an evident next step in the progression of this research.…”
Section: Discussionmentioning
confidence: 99%
“…From a stress-coping perspective, young adults who do not have the resources or ability to engage in problem-focused coping may instead rely on more avoidant or negative coping mechanisms (e.g., negative health behaviors) when dealing with the stress and negative affect that arise from discriminatory experiences (Borrell et al, 2010; Clark et al, 2015; Gerrard et al, 2012). Young adults who experience stress and negative emotions due to racial discrimination may focus on the “quick fix” that alcohol use and sex offer (Elkington et al, 2010; Pascoe & Smart Richman, 2009).…”
Section: Potential Mechanisms Linking Racial Discrimination To Healthmentioning
confidence: 99%
“…Several studies have found that reactions to racial exclusion and past racial discrimination included heightened levels of negative affect (Chow, Tiedens, & Govan, 2008; Clark et al, 2015; Gibbons et al, 2004; 2012; 2014; Hurd et al, 2014; Pascoe & Smart Richman, 2009). Longitudinal research with Black adolescents from FACHS found that anger/hostility mediates the relation between past racial discrimination and substance use cognitions and behaviors (Gibbons et al, 2010; 2012; 2014) and negative affect (depression and anxiety) mediate prospective relations between racial discrimination and risky sex behaviors (Roberts et al, 2012) and substance use (Gibbons et al, 2004).…”
Section: Potential Mechanisms Linking Racial Discrimination To Healthmentioning
confidence: 99%